Re-planning In Home Healthcare: A Decomposition Approach To Minimize Idle Time For Workers While Ensuring Continuity Of Care. Issue 13 (2019) - Martinez, C.; Espinouse, M-L.; Mascolo, M. Di
Abstract: Scheduling and routing careworkers is a perpetual challenge in the home health care (HHC) industry: it is essential to ensure a good quality of care under reasonable expenses. HHC consists in providing care to fragile people, therefore the pool of patients often changes: the schedule must be computed again, but continuity of care must be preserved to keep the patients satisfied. The working environment in the HHC field is remarkably stressful therefore it causes a high turnover rate in the staff, and has a strong impact on service quality. It is crucial to provide schedules that satisty both patients and careworkers. In this paper, we address a weekly home health care re-planning problem with continuity constraints. A decomposition approach is proposed to offer a careworker-friendly solution: first a path-generation algorithm creates admissible tours, and then a set partitioning model selects the tours.